Identification of maternal allele sequences of IG-DMR that are essential for neonatal viability - Satoshi Hara; Akari Muramatsu; Miho Terao; Shuji Takada (PLoS ONE, 2025)
The expression of imprinted genes in the Dlk1-Dio3 domain is regulated by Dlk1-Meg3 intergenic DMR (IG-DMR), which is methylated in a parental-of-origin-specific manner. An unmethylated 4.1-kb region in the IG-DMR is essential for the maternal allele. Several molecular mechanisms have been proposed for the 4.1-kb region of IG-DMR; however, the sequence in the 4.1-kb region essential for imprinted gene expression is still unknown. To explore the sequence responsible for the IG-DMR in vivo, we generated mutant mice with a series of IG-DMR deletions. We observed that a deletion of the 2.7-kb region, including the IG-DMR transcriptional regulatory element (IGTRE), on the maternal allele causes IG-DMR dysfunction, resulting in perinatal lethality. At least two functional sequences exist in IGTRE that are functionally redundant in vivo, and the paternal transmission of a mutant allele, in which IGTRE was deleted together with a tandem repeat sequence in IG-DMR (IGRep), rescued embryonic lethality due to a lack of paternal IGRep. Our findings revealed that a sequence responsible for the lethal phenotype of the maternally inherited 4.1-kb deletion of IG-DMR is in the IGTRE domain.